Solar-Type Activity in Main-Sequence Stars - Gershberg, Roald E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
Solar-type activity over the whole range of the electromagnetic spectrum is a phenomenon inherent in the majority of low- and moderate-mass main sequence stars. In this monograph observational results are summarized in a systematic and comprehensive fashion. The analysis of the various manifestations of such stellar activity leads to the identification of these phenomena with macroscopic non-linear processes in a magnetized plasma. Comparative study of flare stars and the Sun has become increasingly fruitful and is presently an active field of research involving stellar and solar physicists, experts in plasma physics and high-energy astrophysicists. This book will provide them with both an introduction and overview of observational results from the first optical photometry and spectroscopy, from the satellite telescopes International Ultraviolet Explorer to Hubble Space Telescope, XMM-Newton and Chandra, as well as with the present physical interpretation of solar-type activity in main sequence stars. Gershberg's 40-year career studying UV Cet type stars and related objects enables him to provide readers with expert insight into the characteristics of such stars in both the quiescent state and during flares and the reliability of the data over the electromagnetic spectrum and wide temporal scales.
Introduction -- Flare Stars in a Quiescent State: General Characteristics of Flare Stars -- Photospheres -- Chromospheres and Transition Regions -- Coronae and Stellar Winds -- Heating Mechanisms for Stellar Atmospheres -- Flares: General Description of Stellar Flares -- Temporal Characteristics of Flares -- Flare Energy -- Dynamics and Radiation Mechanisms of Flares -- Models of Stellar Flares -- Long-Term Variations in Activity of Flare Stars: Activity Cycles -- Evolutionary Changes -- Conclusion: Activity and Subphotospheric Magnetic Fields -- Activity and Magnetism of Stellar Atmospheres -- References.
Keywords: Astrophysics; Observations, Astronomical; Astronomy—Observations.; Astrophysics and Astroparticles; Astronomy, Observations and Techniques